Exploring Structural, Sociocultural, and Individual Barriers to Alcohol Abuse Treatment Among Hispanic Men - Luis A. Valdez PhD, MPH; David O. Garcia PhD; John Ruiz PhD; Eyal Oren PhD; Scott Carvajal PhD (American Journal of Men's Health, 2018)
Hispanic men have poor access to alcohol abuse treatment, low treatment engagement, and low treatment completion rates despite the contrasting burden of alcohol-related consequences they face. The purpose of this study was to examine Hispanic male perspectives regarding alcohol abuse treatment-seeking behaviors and the structural, sociocultural, and individual factors that may influence initiation and continued engagement in treatment in this population. Individual interviews were conducted with a sample of 20 Hispanic men (age: 44.6 ± 11.3 years). Thematic analysis was completed using a hybrid deductive–inductive approach centered in an a priori codebook that was further supplemented with iterative exploration of transcripts. Results suggested treatment-seeking behaviors were highly influenced by (a) structural factors related to poor treatment access, as well as lack of linguistic- and cultural-responsiveness of available treatment; (b) sociocultural factors related to difficulties problematizing alcohol abuse due to lack of community awareness, societal normalization of consumption, and stigmatization of alcohol abuse treatment; and (c) individual factors related to lack of individual knowledge. This work highlights the perceived lack of congruency between available treatment and the linguistic, cultural, and gender norms of Hispanic men. There is need for responsive treatment strategies that comprehensively consider the gendered- and sociocultural-factors that govern treatment seeking and engagement behaviors. Findings also suggest a need for targeted alcohol abuse awareness building efforts in the Hispanic community. Specifically, the detrimental effects of alcohol-related problems and potential benefits of treatment should be addressed in order to diminish social stigma of abuse and of treatment.